EFFECT OF REPEATED LOADS ON MODULUS OF ELASTICITY FOR FIBER REINFORCED CONCRETE - Salwa M. Abdullah (Tikrit Journal of Engineering Sciences, 2015)
In this research the effect of repeated loads on the initial modulus of elasticity for the fiber reinforced concrete was studied by casting six standard cylinders specimen (150*300mm) for every ratio of fiber, three volume ratios of steel fiber (0,0.4,0.8,1.2)%,were used after 28 days the specimen was tested choosing mix with water cement ratio that gives slump about (80-100) mm. The modulus of elasticity for fiber reinforced concrete cylinders at 28 days for the same ratio were tested by applying load on the three specimens until failure. The other specimens was studied under loads ratio (50%, 60%,75%) from the ultimate load under 25 repeated load then the stress-strain curve was found until load failure. The modulus of elasticity was calculated from the linear part of the stress-strain relationship